(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article clarifies the essence and features of the digital economy. It was found (according to the European Commission) that Denmark, Sweden and Finland have taken the lead in the digital economy over the last three years; the lowest level of digitization is in Bulgaria, Romania and Greece. The necessity of development and introduction of the system of financial and economic security of the enterprise in the conditions of development of digital economy is substantiated. The essence of the concept of financial and economic security of the enterprise in the conditions of digitalization as protection of activity of the enterprise from external and internal negative factors and introduction of innovative information technologies and software for the purpose of its stable and dynamic development is defined. The priority directions of ensuring the financial and economic security of enterprises in the new realities of digitalization of economic activity are given.